2020
DOI: 10.29333/ejgm/8232
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak: Application of Multi-gene Genetic Programming to Country-based Prediction Models

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a novel coronavirus that has infected more than 2,900,000 individuals worldwide. The widespread of coronavirus 2019 (COVID-19) brings about the need for a prediction model to adopt appropriate evidence-based strategies. In this study, multi-gene genetic programming (MGGP), as one of the artificial intelligence models, has been proposed for the first time for predicting the COVID-19 outbreak. Although this is a challenging task due to significant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 22 publications
1
43
0
2
Order By: Relevance
“…Therefore, an investigation similar to the one conducted in this study is suggested in favor of finding the best ANN-based model for a specific country, while the 14th model is found to be adequate in the absence of such analysis. The need for the quest for a country-based prediction model is in agreement with the previous studies [ 5 , 13 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, an investigation similar to the one conducted in this study is suggested in favor of finding the best ANN-based model for a specific country, while the 14th model is found to be adequate in the absence of such analysis. The need for the quest for a country-based prediction model is in agreement with the previous studies [ 5 , 13 ].…”
Section: Discussionsupporting
confidence: 86%
“…Despite numerous advantages of prediction models, they have inevitable limitations. Since these predictions are based on the reported data, they underestimate the confirmed cases either due to the neglecting asymptomatic patients or limited sources of case findings in some countries [ 13 ]. Moreover, developing an ANN-based prediction model, which considers previous fourteen days, reduces fourteen-day records from ANN train data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [495] , a genetic algorithm is used with a cross-validation method to generate a model of the epidemic in Algeria. A multi-gene genetic programming algorithm is proposed in [496] , as a model to predict covid-19 outbreak. In [497] , a combination of virus optimization algorithm with ANFIS is proposed to investigate the effect of various climate-related factors and population density on the spread of the virus.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%